PENGARUH PROMOSI KREDIT PRODUKTIF DALAM MENINGKATKAN JUMLAH NASABAH DI PT BANK LAMPUNG - Willy Radinal; Mery Aryani (ANALISIS, 2021)
Promotion is one of the important variables for companies in increasing sales, marketing and attracting public interest. PT Bank Lampung as a banking company also carries out promotional activities in marketing its products, namely productive credit. However, in reality, the promotion of productive credit has not been optimal. This can be seen from the unstable growth in the number of customers in productive credit financing, even stagnation and a decrease in the number of new customers. The purpose of this study was to determine whether promotion had an effect on increasing the number of productive credit customers at PT Bank Lampung (Main Branch Office). This research used associative quantitative research methods, with data collection techniques using a questionnaire as the primary method, and documentation as research support. The data analysis technique used a simple linear regression test. The results showed; There was a positive and significant influence of the promotional variable (X) on the customer variable (Y), the t-count was 5.265, and the t-table was 2.028, which meant the t-count > t-table, or t-count 5.265 > 2.028. Based on the t-test value, it can be concluded that the proposed hypothesis regarding the effect of promotion on the increase in the number of customers at PT Bank Lampung is acceptable.